Cognitive function and pseudoexfoliation syndrome: the Beijing Eye Study 2011 - You, Qi Sheng; Wang, Ya Xing (British journal of ophthalmology, 2013)
Previous studies have suggested that pseudoexfoliation syndrome could be associated with Alzheimer's disease, since pseudoexfoliation syndrome has some features in common with Alzheimer's disease, in that amyloid-associated proteins occur in association with both diseases.1-3 Since the major limitation of these studies was their design as hospital-based investigations with the potential bias due to the selection of patients, we addressed the question on a potential association between pseudoexfoliation syndrome and Alzheimer's disease in a population-based study. We assessed cognitive function as a measure for Alzheimer's disease. - - The Beijing Eye Study 2011 is a population-based cross-sectional study in a rural region and an urban region of Greater Beijing.4 ,5 The Medical Ethics Committee of the Beijing Tongren Hospital approved the study protocol. The only eligibility inclusion criterion was an age of >50 …
Gesehen am: 23.10.2014